KUALITAS INFORMASI SISTEM KEUANGAN DESA PASCA PENGEMBANGAN APLIKASI - Intan Rakhmawati; Siti Atikah (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2020)
The village government in the West Nusa Tenggara region has implemented village financial management through application of Village Financial System - Sistem Keuangan Desa (Siskeudes). The application has been repaired and updated several times. This study aims to determine the comparison of information quality of village financial system, when operated with Siskeudes V1.0.R1.06 with Siskuedes V2.0. R.0.1, based on Permendagri Number 20 Year 2018. The researcher conducted a content analysis by comparing the outputs of the two Siskeudes versions. Assessment of the quality of the process and information 2 Siskeudes version were analyzed by interpretive methods. The results showed that information quality from Siskeudes Version 2.0 R.0.1. better and integrated with documents at the planning and budgeting stages, compared with previous version Siskeudes. It caused of Siskeudes version 2 already have using activity package in the expenditure, so the village must be able to estimate the expenditure that will be absorbed by each activity. In Siskeudes version 2, in the reporting stage, there have also been additional reports at tax report, because it also adjusts with Minister of Finance Regulation (PMK) Number 193/PMK.07 / 2018. On Siskeudes Version 2.0 R.0.1., have also used OM-SPAN for reporting to the ministry. The results of this study are expected to be useful for the Community and Village Empowerment Agency (DPMD) to train verifiers at the sub-district level.